Unusual Late Relapse of ALK-Positive Anaplastic Large Cell Lymphoma Successfully Cleared Using the ALK-Inhibitor Crizotinib: Case Report - Harrer, Dennis Christoph; Menhart, Karin; Mayer, Stephanie; Herr, Wolfgang; Reichle, Albrecht; Vogelhuber, Martin (Frontiers in Oncology, 2020)
Anaplastic large cell lymphoma (ALCL) with ALK-translocation constitutes an aggressive lymphoma with high sensitivity to anthracycline-based chemotherapy. Relapse, however, is observed in about one-third of patients. Salvage treatment incorporates high-dose chemotherapy followed by autologous or allogeneic stem cell transplantation, treatment with the CD30-specific immunoconjugate Brentuximab vedotin (BV) and the use of ALK-inhibitors, such as crizotinib. In this case report, we present a patient with a rare late relapse of ALK-positive ALCL following chemotherapy, who was neither eligible for high-dose chemotherapy nor treatment with BV. Relapse therapy was carried out with daily crizotinib, which rapidly mediated complete regression of all ALCL manifestations. In light of few clinical trials published on the use of crizotinib against ALCL, we want to further substantiate the efficacy of crizotinib as salvage therapy in patients with relapsed ALCL especially if ineligible for high-dose chemotherapy or BV treatment. Finally, we would like to enhance vigilance for potential late relapse of ALCL more than a decade after frontline treatment.